KAMPANYE PENINGKATAN PENGETAHUAN MAHASISWA UNDIP, UDINUS, DAN UNIKA TENTANG BUS WISATA KOTA SEMARANG SEBAGAI ALTERNATIF STRESS RELIEF - Alisya Lingga Maghfira; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Academic pressure often cause students to experience high levels of stress, creating a need foralternative stress relief activities. The Semarang City Tour Bus, provided by the Semarang CityGovernment, has the potential to serve as both a recreational facility and an educationalmedium to introduce various tourist destinations in Semarang. However, students’ level ofknowledge of this service remains relatively low. Therefore, this professional project aims toincrease the knowledge and interest of students from Diponegoro University, Dian NuswantoroUniversity, and Soegijapranata Catholic University in the Semarang City Tour Bus as analternative stress relief. The campaign team designed a communication strategy by integratingcyber public relations, advertising, event and experiences, and collaboration with Key OpinionLeaders (KOL). The team delivered campaign messages through Instagram and a series ofevents as the main communication channels by applying the AISAS Model. In itsimplementation, the author carried out the roles of strategist planner, event manager, anddirector. The campaign results show an increase in student knowledge from 20% to 87.6% andsuccessfully collected a total of 537 student databases throughout the campaign activities